ANALISIS PEMAHAMAN KONSEP SASTRA ANAK PADA MAHASISWA S1 PGSD DALAM PERKULIAHAN PENDIDIKAN SENI TARI DAN DRAMA: ANALISIS PEMAHAMAN KONSEP SASTRA ANAK PADA MAHASISWA S1 PGSD DALAM PERKULIAHAN PENDIDIKAN SENI TARI DAN DRAMA - Bening Sri Palupi; Putri Meinita Triana (Bangun Rekaprima, 2025)
Dance and drama education is very important for PGSD S-1 students as a pedagogical provision for prospective teachers to teach children's literature in elementary school. This research is a descriptive qualitative research that aims to analyze the understanding of children's literary concepts in PGSD S-1 students in dance and drama education lectures. The data collection technique used a questionnaire which was then analyzed by the data analysis of the Cresswell model. The results showed that most students had a good understanding of children's literature, namely 96.5% and 98.% of students stated an increase in understanding through drama performance arts activities. In addition, 98.9% of students feel more able to identify elements of children's stories after practicing drama. The integration of performing arts also increases the interest of all students in children's literature learning. Therefore, it is necessary to strengthen performance arts-based learning strategies as an effort to improve children's literary literacy in the university environment. Thus, increasing student literacy towards children's literature can be achieved optimally because it is accompanied by innovation and continuous evaluation.